Revisiting Authenticity in the Age of the Digital Transformation of Cultural Tourism - Shehade, Maria; Stylianou-Lambert, Theopisti (My University, 2020)
The recent years have seen a digital transformation of the cultural tourism sector and the interpretation of cultural heritage, through the use of emerging and immersive technologies, such as Virtual Reality (VR) and Augmented Reality (AR). Although this transformation has brought important advantages, it may also challenge the authenticity of the offered experience. This paper aims to explore the different and conflicting scholarly debates on authenticity and technology, which lie at the intersection of three fields, namely tourism studies, heritage studies and ICT and which may also have consequences on the actual applicability of such technologies in cultural tourism. An examination of the concept of authenticity in the aforementioned disciplines is provided, through an analysis of how the concept has evolved in each of the three disciplines. The paper also highlights their differences and points of convergence and discusses the challenges and implications created by the identified discrepancies between the different stakeholders involved in cultural tourism. Finally, suggestions will be offered on how the discussed challenges and implications can be addressed in light of the new needs of cultural tourism in the digital era.
Keywords: Authenticity; Cultural tourism; Virtual reality; Emerging technologies; Cultural heritage; Authority